The vision of haptics tunes the somatosensory threshold - Del Vecchio, Maria; De Marco, Doriana; Pigorini, Andrea; Fossataro, Carlotta; Cassisi, Annalisa; Avanzini, Pietro (Neuroscience letters, 2022)
•The vision of haptics enhances tactile sensitivity, even if implied.•VET may occur within posterior perisylvian regions.•Specific visual stimuli might sustain tactile awareness, vicariating impaired functions. The interaction between different sensory modalities represents a crucial issue in the neuroscience of consciousness: when the processing of one modality is deficient, the concomitant presentation of stimuli of other spared modalities may sustain the restoration of the damaged sensory functions. In this regard, visual enhancement of touch may represent a viable tool in rehabilitating tactile disorders, yet the specific visual features mostly modulating the somatosensory experience remain unsettled. In this study, healthy subjects underwent a tactile detection task during the observation of videos displaying different contents, including static gratings, meaningless motions and natural or point-lights reach-to-grasp-and-manipulate actions. Concurrently, near-threshold stimuli were delivered to the median nerve at different time-points. The subjective report was collected after each trial; the sensory detection rate was computed and compared across video conditions. Our results indicate that the specific presence of haptic contents (i.e., the vision of manipulation), either fully displayed or implied by point-lights, magnifies tactile sensitivity. The notion that such stimuli prompt a conscious tactile experience opens to novel rehabilitation approaches for tactile consciousness disorders.